A new RP- HPLC Method Development and Validation for the Concurrent Identification of Nivolumab and Hyaluronidase in Bulk and Pharmaceutical Dosage Form - G, Navya Sri; Dr.S, Sujatha; D, Anusha; K, Susmitha; sultana, Tahseen; V, Saritha (Asian Journal of Chemical and Pharmaceutical Research, 2025)
A robust HPLC method was developed and validated for the simultaneous estimation of Nivolumab and Hyaluronidase using an Inspire C18 column (250×4.6 mm, 5µm) with a 1.0 mL/min flow rate. The method achieved clear separation with retention times of 2.817 min (Nivolumab) and 3.731 min (Hyaluronidase). System suitability, linearity (R²> 0.999), precision (%RSD low), and accuracy (98–102% recovery) met validation standards. The method demonstrated good ruggedness, robustness, and sensitivity, with LOD/LOQ values of 1.24µg/mL and 0.04µg/mL, respectively. Intermediate precision confirmed reproducibility across systems. This validated method is suitable for routine quality control and regulatory compliance in pharmaceutical formulations.